(untitled) (Africa Development, 2021)
Contents Editorial Vusi Gumede................................... 1 Genealogies of Coloniality and Implications for Africa’s Development Sabelo J. Ndlovu-Gatsheni....................... 13 No African Futures without the Liberation of Women: A Decolonial Feminist Perspective Akhona Nkenkana................................ 41 The Global Economic Crisis and the Africa Rising Narrative Devan Pillay..................................... 59 Brazil, Russia, India, China, and South Africa (BRICS) and Africa: New Projected Developmental Paradigms Tukumbi Lumumba-Kasongo..................... 77 Emerging Questions on the Shifting Sino-Africa Relations: ‘Win-Win’ or ‘Win-Lose’? Phineas Bbaala................................... 97 Politics of Financialisation and Inequality: Transforming Global Relations for Inclusive Development Samuel Oloruntoba............................... 121 Development is Resistance Yash Tandon........................................ 139